Review of the Second Quarter of the Year - Persons, Warren M. (The Review of Economics and Statistics, 1922)
T HE opening quarter of I92I was characterized by general depression and continued liquidation in most lines of trade; but it brought a turn of the tide in a few industries, like textiles and boots and shoes, 'which had been among the first to readjust themselves to changed conditions, and it saw a slackening of the precipitate drop of wholesale commodity prices. April witnessed some revival of speculative activity accompanied with an increased volume of trade in some other lines, which, however, proved later to be largely of a seasonal character. Upon the whole, the developments of that'month were distinctly encouraging; but May and June brought reversals of the upward trend in various industries, renewed liquidation in security markets, and a generally pessimistic sentiment which at times became decidedly, although somewhat vaguely, apprehensive. Upon the whole, the second quarter of I92I disappointed the expectations which were entertained quite generally early last April. The bad developments, which almost monopolized attention in May and June, were greater depression in the iron and steel industry; decreased activity in the automobile trade; unsettlement of the foreign exchanges; a sharp decline of exports; recessions of prices of oil, hides, leather, grain, live stock, and various non-ferrous metals, some of which had previously seemed to have reached a point of stabilization; increased unemployment in most sections of the United States; and renewed liquidation in securities which brought new low levels in the prices of both railroad and industrial stocks. The causes of these unsatisfactory conditions were partly of domestic origin and partly foreign. The chief of them seem to be: (a) the partial dislocation of international trade and finance, (b) the unequal readjustment of prices and production in different branches of industry, and (c) persistent money strain. Most of the contributing factors to the trade depression of the second quarter either admit of reduction to these terms, or, in one way'or another, derive their importance very largely from conditions produced by the three fundamental causes. The dislocation of international trade and finance results, firstly, from Europe's temporary inability to purchase her accustomed amount of the products of the rest of the world; and, secondly, from the fact that various European countries are heavily in debt to the United States, while, as the result of the reparations settlement, Germany is heavily indebted to various other'European countries. Even if the war had not left this troublesome legacy of enormous international debts which never could have come into existence under normal conditions, the temporary reduction of Europe's purchasing power would have disturbed seriously the international exchanges; but the cumulative effects of the two factors have produced a situation which will cause constant trouble for many years unless, as now seems unlikely, it is relieved by a major operation of financial surgery. The year I920 saw a marked increase of exports from Great Britain, France, and Italy, indicative of improved economic conditions and a gradual restoration of ability to pay for foreign imports. So far during I92I the reported value of exports has not increased, and in England, on account of labor difficulties, it has rather sharply declined. Lower export prices undoubtedly account in some measure for this result, but the rate of improvement since the end of the war has been discouragingly slow. Upon the whole, Europe is not yet able to trade with the rest of the world upon pre-war terms and is, therefore, still further from being in a position to meet her current obligations to the United States. The German reparation payments may tend in time to improve the international position of the countries that are to receive them, but their first effects have been to unsettle the foreign exchanges, the constant fluctuation of which already constituted a serious embarrassment to the trade of the world. In June the decline of European rates of exchange due to Germany's purchases of dollar exchange tended to cause unsettlement and reacted unfavorably upon our export trade. In the course of time, as things become adjusted to continuing reparation payments, the periodical settlements may be effected with less disturbance than was caused at the start. But it is clear that the mechanism of international exchange, which has not yet begun to function normally, will hereafter be subject to a new disturbing influence the effect of which will be farreaching. All this was to be expected, as the history of the French indemnity in I87I abundantly proved. But since the whole matter of reparations involved so much uncertainty, it had not been taken definitely into account; and it, therefore, produced a marked effect upon business sentiment during the last of May and the early part of June. Turning to the disturbing factors of domestic origin, it is clear that the continued depression of the second quarter was due in considerable part to the slow and uneven progress of liquidation in different lines of trade. Reduction of excessive stocks of goods in several lines went on slowly, the writing down of inventories continued, and floating indebtedness was in numerous cases converted into funded debt thereby reducing current obligations. These things tended, of course, to improve the general situation, but did not make for cheerfulness while they were going on since they meant the acceptance of the fact of heavy losses or occasioned a continued demand for capital. We still have a situation in which many commodity Drices are out of